HUBUNGAN ASUPAN IODIUM DAN GOITROGENIK DENGAN GONDOK PADA ANAK SD JRAHI KECAMATAN GUNUNGWUNGKAL KABUPATEN PATI - Nurdianti; Maryanto, Sugeng (UNIVERSITAS NGUDI WALUYO, 2012)
Iodine deficiency disorder (IDD) is still a problem in Indonesia. Goiter is one of its manifestations. The main cause is not sufficient iodine in food intake, can also be caused by the influence of goitrogen. Gunungwungkal Sub-district is an endemic region with goiter prevalence of 32.33% on the schoolchildren. The purpose of this study was to find the correlation between iodine and goitrogen intakes on schoolchildren This was a discriptive and correlational study with cross sectional approach. The population in this study was 227 schoolchildren at Jrahi 01 and 02 Elementary School. The sampling technique used purposive sampling with the samples as many as 66 schoolchildren. This study instrument used the form of food frequency questionnaire (FFQ) to assess iodine and goitrogen intakes incidences and palpation examination. The data analysis used Kendall Tau test with Î± = 0.05. The results of this study indicated correlation between iodine intake and goiter on the schoolchildren (p = 0.001). There was a correlation between goitrogen intake and goiter on school children (p = 0.042). It is concluded that there was correlation between iodine and goitrogen intakes with goiter on the schoolchildren. It is recommended to increase iodine intake (either from iodized food sources or iodized salt) to prevent goiter. Keep goitrogen souce foods, but with attention to appropriate processing methods. Abstrak : Gangguan Akibat Kekurangan Iodium (GAKI) masih menjadi masalah di Indonesia. Gondok merupakan salah satu manifestasinya. Penyebab utamanya adalah tidak kecukupan iodium dalam makanan, dapat juga disebabkan oleh pengaruh goitrogenik. Kecamatan Gunungwungkal merupakan salah satu kecamatan endemis dengan prevalensi gondok anak sekolah 32,33%. Tujuan penelitian ini untuk mengetahui hubungan asupan iodium dan goitrogenik dengan gondok pada anak SD. Jenis penelitian ini adalah penelitian deskriptif dan korelasional dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah 227 siswa SD Jrahi 01 dan 02. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah sampel 66. Instrumen yang digunakan adalah : formulir food frequency questionnaire (FFQ) untuk mengetahui asupan iodium dan goitrogenik dan pemerikasaan palpasi. Teknik analisis data yang digunakan adalah uji Kendall Tau dengan Î±= 0,05 Hasil penelitian menunjukkan ada hubungan asupan iodium dengan gondok pada anak SD (p= 0,001). Ada hubungan asupan goitrogenik dengan gondok pada anak SD (p= 0,042). Kesimpulan ada hubungan antara konsumsi asupan iodium dan goitrogenik dengan gondok pada anak SD. Disarankan, perlu adanya arahan pada anak SD bahwa mengkonsumsi makanan sumber iodium dan garam beriodium penting untuk mencegah terjadinya gondok. Tetap mengkonsumsi makanan sumber goitrogenik namun dengan memperhatikan cara pengolahan yang tepat.